Tantangan Dakwah Tradisional di Era Digital : Analisis Prilaku Remaja Dilihat Dari Rendahnya Partisipasi Pengajian Mingguan - Umar Alfaruq (Educational Journal, 2026)
This research is driven by the phenomenon of digital disruption, which has led to low participation among adolescents in weekly religious gatherings (pengajian). Despite the vital role of these gatherings in character building, a gap has emerged between monotonous traditional preaching methods and the interactive, visual digital lifestyles of modern youth. This study aims to evaluate the challenges of traditional da'wah and analyze shifts in adolescent behavior in the digital era to prevent a disconnect in the transmission of Islamic values. Using a qualitative approach with a descriptive design, data were collected through technical triangulation, including participant observation, documentation, and in-depth interviews with the adolescent population at the research site. The results indicate that the low level of engagement is not caused by a loss of religiosity, but rather by psychological and social alienation from their environment, others, or even themselves. This is a result of one-way lecture methods that clash with the cognitive structures of today's adolescents, who possess a short attention span. The study found highly intensive smartphone usage, 3–18 hours/day, dominated by the TikTok platform as a source of instant gratification. Adolescents tend to perceive conventional gatherings as boring and rigid compared to short, relevant digital da'wah content. The research concludes that the future of moral regeneration in rural areas heavily depends on the adaptability of da'wah institutions in reforming communication styles to be more popular, inclusive, and interactive, as well as modernizing mosque infrastructure, such as providing Wi-Fi facilities, to enhance da'wah relevance for digital natives.